Vigour of Competency based medical education (CBME) (GAIMS Journal of Medical Sciences, 2022)
Competency based medical education (CBME) was introduced by the Medical Council of India (MCI, now called as National Medical Commission, NMC) from 2019 batch across the India. CBME was rolled over to provide effective outcome based strategy and to develop the framework of competencies.  Before its introduction, we were following the traditional medical curriculum put forward by Regulations on Graduate Medical Education, 1997. A strong need of change in the traditional curriculum was felt by many educationalists across the nation. This was the basis of emergence of CBME.